Degradation of collagen I by activated C1s in periodontal Ehlers-Danlos Syndrome - Amberger, Albert; Pertoll, Johanna; Traunfellner, Pia; Kapferer-Seebacher, Ines; Stoiber, Heribert; Klimaschewski, Lars; Thielens, Nicole; Gaboriaud, Christine; Zschocke, Johannes (Frontiers in Immunology, 2023)
Periodontal Ehlers-Danlos syndrome (pEDS) is an autosomal dominant disorder characterized by early-onset periodontitis leading to premature loss of teeth, lack of attached gingiva and thin and fragile gums leading to gingival recession. Connective tissue abnormalities of pEDS typically include easy bruising, pretibial plaques, distal joint hypermobility, hoarse voice, and less commonly manifestations such as organ or vessel rupture. pEDS is caused by heterozygous missense mutations in C1R and C1S genes of the classical complement C1 complex. Previously we showed that pEDS pathogenic variants trigger intracellular activation of C1r and/or C1s, leading to extracellular presence of activated C1s. However, the molecular link relating activated C1r and C1s proteases to the dysregulated connective tissue homeostasis in pEDS is unknown. Using cell- and molecular-biological assays, we identified activated C1s (aC1s) as an enzyme which degrades collagen I in cell culture and in in vitro assays. Matrix collagen turnover in cell culture was assessed using labelled hybridizing peptides, which revealed fast and comprehensive collagen protein remodeling in patient fibroblasts. Furthermore, collagen I was completely degraded by aC1s when assays were performed at 40°C, indicating that even moderate elevated temperature has a tremendous impact on collagen I integrity. This high turnover is expected to interfere with the formation of a stable ECM and result in tissues with loose compaction a hallmark of the EDS phenotype. Our results indicate that pathogenesis in pEDS is not solely mediated by activation of the complement cascade but by inadequate C1s-mediated degradation of matrix proteins, confirming pEDS as a primary connective tissue disorder.